2022
DOI: 10.1186/s12955-022-01926-w
|View full text |Cite
|
Sign up to set email alerts
|

Detection of response shift in health-related quality of life studies: a systematic review

Abstract: Background Response Shift (RS) refers to the idea that an individual may undergo changes in its health-related quality of life (HRQOL). If internal standard, values, or reconceptualization of HRQOL change over time, then answer to the same items by the same individuals may not be comparable over time. Traditional measures to evaluate RS is prone to bias and strong methodologies to study the existence of this phenomenon is required. The objective is to systematically identify, analyze, and synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…To further find the field of response shift research, this study described variation in prevalence of response shift results and where possible, magnitude of response shift effects for quantitative studies using PROM data. Consistent with earlier reviews [ 7 , 10 ], the most frequently applied response shift method was the then-test, followed by SEM, other design-based methods, regression methods without classification, individualized methods, regression methods with classification, IRT/Rasch, and other study-specific methods. Most studies reported detection of one or more response shift effects.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…To further find the field of response shift research, this study described variation in prevalence of response shift results and where possible, magnitude of response shift effects for quantitative studies using PROM data. Consistent with earlier reviews [ 7 , 10 ], the most frequently applied response shift method was the then-test, followed by SEM, other design-based methods, regression methods without classification, individualized methods, regression methods with classification, IRT/Rasch, and other study-specific methods. Most studies reported detection of one or more response shift effects.…”
Section: Discussionsupporting
confidence: 60%
“…Of these studies, 82 (85.4%) detected recalibration response shift, 20 studies (20.8%) detected reprioritization response shift, four studies (4.2%) detected reconceptualization response shift, and seven studies (7.3%) reported a general response shift effect without indicating a particular pathway. A more recent systematic review of 107 studies, also using quantitative methods, which were published between 2010 and 2020 [ 10 ] found that only 91 studies (70.5%) had detected response shift. Less than half of the studies (51 studies) overlapped with the former review by Sajobi et al [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative explanations include improved patient satisfaction through interactions with home medical care providers and improved QOL caused by reduced pain and other symptoms through appropriate palliation [ 5 , 31 ]. A further alternative explanation is a response shift to QOL-HC due to changes in internal standards and values accompanying repeated reflections on their lives [ 32 ]. In applying the results of this study to clinical practice, physicians should keep in mind that the patients might have lost their sense of purpose in life and hope for health.…”
Section: Discussionmentioning
confidence: 99%
“…As patients and families become familiar with dialysis tasks and schedules, there is a shift in expectation, potentially leading to QoL improvements that overstate the benefits. This adaptation or response shift is well described and common in longitudinal studies of patients with chronic disease (7,8). In brief, response shift theory, as applied to longitudinal QoL assessment, describes changes that occur over time as patients re-evaluate the meaningfulness of their lives.…”
mentioning
confidence: 82%